2002
DOI: 10.1007/bf03402019
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Analogs of Green Tea Polyphenols as Proteasome Inhibitors

Abstract: Background: Animal, epidemiological and clinical studies have demonstrated the anti-tumor activity of pharmacological proteasome inhibitors and the cancer-preventive effects of green tea consumption. Previously, one of our laboratories reported that natural ester bond-containing green tea polyphenols (GTPs), such as (Ϫ)-epigallocatechin-3-gallate [(Ϫ)-EGCG] and (Ϫ)-gallocatechin-3-gallate [(Ϫ)-GCG], are potent and specific proteasome inhibitors. Another of our groups, for the first time, was able to enantiosel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 45 publications
8
116
1
Order By: Relevance
“…Green tea and the risk of adult leukaemia M Zhang et al significant dose -response relationships, the first such evidence, although a US hospital-based case -control study recently reported a negative association between black tea and AML in women (Li et al, 2006). Our findings are consistent with experimental evidence that green tea polyphenols inhibited proteasome and induced apoptosis in leukaemic cells (Smith et al, 2002).…”
Section: Number Of Cupssupporting
confidence: 88%
“…Green tea and the risk of adult leukaemia M Zhang et al significant dose -response relationships, the first such evidence, although a US hospital-based case -control study recently reported a negative association between black tea and AML in women (Li et al, 2006). Our findings are consistent with experimental evidence that green tea polyphenols inhibited proteasome and induced apoptosis in leukaemic cells (Smith et al, 2002).…”
Section: Number Of Cupssupporting
confidence: 88%
“…Various potential mechanisms contributing to the anticancer effects of (À)-EGCG have been described, including suppression of Wnt signaling (8), blockade of methylation (9), and inhibition of matrix metalloproteinase (10) and the proteasome (11)(12)(13)(14)(15)(16).…”
Section: Biologically Active Components Of Green Tea Include Polyphenmentioning
confidence: 99%
“…Other structure-activity relationship studies evidenced that the A ring and the gallate ester/amide bond are involved in the mechanism of proteasome inhibition [132]. Similar effects have been described for two synthetic enantiomeric analogs of natural GTCs in PCa cells [133]. The observed accumulation of short-lived proteins, normally addressed to proteosomal degradation such as p21, p27, Bax and ikΒα, in PCa cells after EGCG or GTCs treatment indirectly confirms, that GTCs exert inhibitory effect on the proteasome activity [98,134].…”
Section: Proteasome Inhibitionmentioning
confidence: 53%